2018
DOI: 10.1182/blood-2018-99-117167
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD45 with an Amanitin Antibody-Drug Conjugate Effectively Depletes Human HSCs and Immune Cells for Transplant Conditioning

Abstract: Introduction Bone Marrow Transplant (BMT) is a potentially curative treatment for malignant and non-malignant blood disorders and has demonstrated impressive outcomes in autoimmune diseases. Prior to BMT, patients are prepared with high-dose chemotherapy alone or with total body irradiation, and both are associated with early and late morbidities, such as infertility, secondary malignancies and organ toxicity; and substantial risk of mortality. This greatly limits the use of BMT in malignant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Additionally, Moldenhauer et al [184] showed the efficacy of an α-amanitinbased ADC against pancreatic cancer -one of the most aggressive types of cancer there is -in vitro and in mice. Although the data shown in these studies is very limited, αamanitin was able to deplete hematopoietic stem cells by targeting either CD117 [185] or CD45 [186] for subsequent bone marrow transplantation. These qualities make amatoxins one of the currently most promising candidates for novel ADC toxins.…”
Section: "Classic" Adcs: Antibody-small Molecule Toxin Conjugatesmentioning
confidence: 99%
“…Additionally, Moldenhauer et al [184] showed the efficacy of an α-amanitinbased ADC against pancreatic cancer -one of the most aggressive types of cancer there is -in vitro and in mice. Although the data shown in these studies is very limited, αamanitin was able to deplete hematopoietic stem cells by targeting either CD117 [185] or CD45 [186] for subsequent bone marrow transplantation. These qualities make amatoxins one of the currently most promising candidates for novel ADC toxins.…”
Section: "Classic" Adcs: Antibody-small Molecule Toxin Conjugatesmentioning
confidence: 99%
“…Given the promise of antagonistic antibodies to HSCs in enabling hematopoietic chimerism, we and colleagues also began exploring HSC-targeted immunotoxins for this purpose [167,175]. Several different candidate HSC antigens were tested, including anti-CD27, CD45, CD49d, CD84, CD90, CD110, CD117, CD133, CD135, and CD184, but only ckit/CD117 and CD45 have been selected for further study.…”
Section: Anti-hsc Immunotoxins/adcsmentioning
confidence: 99%
“…Naked antibodies targeting CD45 depleted only lymphoid cells and additional genotoxic chemotherapy was required to deplete HSCs [166]. To enhance HSC depletion while avoiding bystander toxicity (neutropenia, lymphopenia, and thrombocytopenia) caused by CD45-radioimmunotherapy, Palchaudhuri et al developed a saporin-based CD45 (CD45-SAP) immunotoxin using a biotin-streptavidin linker [167].…”
Section: Anti-cd45mentioning
confidence: 99%
See 1 more Smart Citation